Prolonged Elevation of D-dimer Levels In The Post- Covid-19 Period - Gulay Aydin; Ebru Golcuk (Haseki Tıp Bülteni)

(untitled)
Aim:D-dimer elevation is observed during acute Coronavirus disease-2019 (COVID-19) and the post- COVID-19 period. It is not known how long the D-dimer remains elevated in the post-COVID-19 period. The aim of the study was to determine how long the D-dimer level remained elevated in the post-COVID-19 period.Methods:This study was conducted as a cross-sectional study, a type of observational study, at the University of Health Sciences Turkey, Darica Farabi Training and Research Hospital Cardiology Outpatient Clinic between March 1, 2022, and December 1, 2022. Past medical histories, examination notes, and laboratory results were extracted from standard electronic medical records. Patients were also categorized as those over 50 years old and those under 50 years old. Age-adjusted D-dimer levels were used when analyzing the D-dimer values of patients over 50 years old.Results:Three hundred twenty two patients were included in this study. Two hundred nineteen (68%) patients were women. Two hundred twenty-three (69%) patients were under the age of 50. Elevated D-dimer levels were present in 77 (23.91%) patients, and age-adjusted elevated D-dimer levels were present in 22 (6.80%) patients. The median duration from the time the patient’s reverse transcription-polymerase chain reaction (RT-PCR) test resulted in a positive result to the time of admission was 6 (1-24) months. The highest number of patient admissions to the cardiology outpatient clinic occurred in the 12th month after the RT-PCR test resulted in a positive.Conclusion:We investigated how long the D-dimer remained elevated in the post-COVID-19 period. We examined the time distribution of D-dimer elevation and calculated age-adjusted D-dimer values. The highest number of patients whose D-dimer level was elevated on admission occurred in the 3rd-4th month after the RT-PCR test resulted positively.